Dysmetabolism and Sleep Fragmentation in Obstructive Sleep Apnea Patients Run Independently of High Caffeine Consumption - Conde, Sílvia V. (2022)
Funding Information: This research was funded by the Portuguese Science and Technology Foundation (FCT) with the grant number CEECIND/04266/2017. Acknowledgments: The authors would like to thank Eunice Silva for technical support. Funding Information: Funding: This research was funded by the Portuguese Science and Technology Foundation (FCT) with the grant number CEECIND/04266/2017.